2017
DOI: 10.1177/0956797617713309
|View full text |Cite
|
Sign up to set email alerts
|

Linking Positive Affect to Blood Lipids: A Cultural Perspective

Abstract: Positive affect (PA) has been associated with better physical health. While PA is highly desirable among Westerners, East Asians tend to deemphasize PA. The present study examined the relations of PA with serum lipid profiles, known to be strongly predictive of cardiovascular disease (CVD) risk, and further tested whether the associations depend on cultural contexts using large probability samples of Japanese and U.S adult populations. As predicted, PA was associated with healthier lipid profiles for Americans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Experimental research supports that East Asians are more likely to believe that being too happy has negative consequences, for example (Miyamoto & Ma, 2011). Reflecting such dialectical beliefs, the links between positive emotions and mental and physical health have been shown to be weaker among Asian samples than among Western samples (Lee, Wang, & Koo, 2011), including between MIDJA and MIDUS respondents (Yoo, Miyamoto, Rigotti, & Ryff, 2016). Thus, the lack of association between hedonic well-being and health outcomes in Japan in the present study is in line with these prior findings.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental research supports that East Asians are more likely to believe that being too happy has negative consequences, for example (Miyamoto & Ma, 2011). Reflecting such dialectical beliefs, the links between positive emotions and mental and physical health have been shown to be weaker among Asian samples than among Western samples (Lee, Wang, & Koo, 2011), including between MIDJA and MIDUS respondents (Yoo, Miyamoto, Rigotti, & Ryff, 2016). Thus, the lack of association between hedonic well-being and health outcomes in Japan in the present study is in line with these prior findings.…”
Section: Discussionmentioning
confidence: 99%
“…A review of findings with lipids reported mixed results (1), but rigorous studies have found higher psychological well-being is associated with more favorable lipid levels (34). It appears that these associations may vary depending on sex and race, as well as cultural differences (35,36). While cross-sectional studies have reported largely null associations of psychological well-being with blood glucose or glycosylated hemoglobin (HbA1c; 1,35), at least one longitudinal study found positive affect was associated with lower HbA1c over 2 years of follow-up (37).…”
Section: Biological Pathwaysmentioning
confidence: 99%
“…Our study examined whether positive affect would be associated with lipids in the United States. where individuals' high levels of positive affect is culturally fitting in Japan where high levels of positive affect are culturally less fitting compared to Western cultures (Yoo, Miyamoto, Rigotti, & Ryff, ). Using Midlife in the United States and Midlife in Japan, we found associations between positive affect and healthy lipid profiles (i.e., high levels of high‐density cholesterols and a low ratio of high‐density cholesterols to total cholesterols) among Americans, but such associations were absent among Japanese participants.…”
Section: Cultural Fit Of Emotions In Healthmentioning
confidence: 99%